A new species, a new name and new synonyms in Euphorbia subg. Esula (Euphorbiaceae ) from South Africa - Bruyns, Peter V. (Phytotaxa, 2019)
A very small species Euphorbia minuscula (Euphorbiaceae) belonging to subg. Esula is described from the southern, coastal part of South Africa. A key to the closely related species is provided and a new name, E. dumosoides, is published for the illegitimate Euphorbia dumosa E. Mey. ex Boissier. Lectotypes are designated for four names. The synonymy of E. natalensis is extended to include E. epicyparissias and E. crebrifolia.